A Study on Continuous Flax Fibre Reinforced Polypropylene Composite in Stamp Forming Process. Issue 4 (July 2013) - Wang, Wentian; Lowe, Adrian; Kalyanasundaram, Shankar
This study investigates the forming behaviour of flax fibre reinforced polypropylene composites through stamp forming. A real time photogrammetric three dimensional strain measuring system was employed to capture the surface motion and compute strain deformation during forming. Failure mechanisms exhibited in the flax/polypropylene composites at different forming temperatures were determined by visual and microscopical examinations. Fibre fracture was identified as the major failure mode. At a forming temperature of 160 °C, fibre pull out was also observed in addition to fibre fracture. A study of forming modes exhibited at various forming temperatures illustrated that there is an optimal temperature window for forming. A key finding from this work is that the matrix shear deformation can aid in superior forming for this class of material systems.